Acute Fatty Liver in Pregnancy - Wirawan, Wahyudi; Setiawan, Dani; Maelissa, Merlin Margreth; Islamy, Nurul; Lumentut, Anastasia Mariane; Puspitasari, Maya Khaerunnisa (Journal La Medihealtico, 2025)
Acute fatty liver in pregnancy (AFLP) is a rare, life-threatening condition that typically occurs in the third trimester, characterized by fat accumulation in the liver. It is associated with high maternal and fetal morbidity, although mortality rates have decreased with improved obstetric care. AFLP's exact cause remains unclear, though it is linked to impaired fatty acid metabolism in the liver. Key risk factors include multiple pregnancies, male fetuses, and metabolic disorders. The condition presents with non-specific symptoms like nausea, jaundice, and abdominal pain, with progression to liver failure and encephalopathy in severe cases. Early diagnosis is critical, and the Swansea Criteria have proven useful. Management focuses on early delivery and supportive care, with cesarean section preferred due to the risk of fetal distress. Liver transplantation may be necessary for severe cases. While maternal and fetal survival rates have improved, the condition still poses significant challenges, emphasizing the need for prompt diagnosis and treatment.